A carboxylated graphene nanodisks/glucose oxidase nanotags and Mn:CdS/TiO2 matrix based dual signal amplification strategy for ultrasensitive photoelectrochemical detection of tumor markers. Issue 24 (15th November 2017) - Song, Jie; Wu, Shuo; Yang, Xinlan; Yuan, Jingli
Abstract : A graphene nanodisk and glucose oxidase based dual signal amplification strategy was developed for a highly sensitive PEC immunoassay of CEA. Abstract : Graphene nanodisks with good conductivity and plenty of edge sites were synthesized to load glucose oxidase (GRD-GOD) and coupled with a Mn 2+ doped CdS quantum dot (QD) modified TiO2 electrode (CdS:Mn/TiO2 ) for a highly sensitive photoelectrochemical (PEC) immunoassay. The specific immune-recognition behaviour can bring the GRD-GOD labelled antigen into the antibody immobilized CdS:Mn/TiO2 interface and dramatically enhance the photocurrent response via a dual signal amplification strategy. First, graphene nanodisks with a strong electron transfer capacity can improve the conductivity of both the insulating protein layers and the CdS:Mn/TiO2 matrix, thus facilitating the regeneration of trapped carriers and hot electrons in the CdS:Mn QD films and enhancing the PEC performance. Second, graphene nanodisks introduce a great number of GOD molecules into a PEC detection process, which catalyze glucose to produce numerous molecules of H2 O2 . The latter act as sacrificial electron donors to scavenge photogenerated holes, retard the electron–hole recombination, and significantly improve the photo-to-electron conversion efficiency. Based on the dual signal amplification strategy and using a carcinoembryonic antigen as a model target, a highly sensitive PEC immunoassay was therefore developed with an extremely low limit of detection of 5.65 fg mL −1 and a rather wide linear range from 10 fg mL −1 to 1 ng mL −1 . The immunoassay showed good reproducibility and stability, as well as good selectivity and high accuracy in serum sample analysis. In this regard, PEC immunosensors may have great application potential for the screening of tumor markers and the prevention and monitoring of serious diseases.